Ministério Público e o Tribunal do Júri: análise da prática de vigilância para a composição do Conselho de Sentença - Silva, Patrícia Cordeiro da (2021)
The work focused on the surveillance practices carried out by the Public Ministry on jurors, in the choice of the Sentencing Council. The corpus of the work was a questionnaire produced by the Public Ministry of Paraná, which was applied by him to more than 600 jurors in the State of Paraná, giving rise to the material called Profile of the Jurors in the Paraná County. For the clipping of this material, the questions were chosen privileging all the topics of the questionnaire. The general objective of the dissertation was to reflect on the continuity of the practice of monitoring the life of the jurors for the composition of the Sentencing Council, and as specific objectives, to analyze the meaning effects of the questionnaire, observing the discursive memory, which appears and updates itself in the enunciation, dialoguing with the implicit statements, and reflect on the discursive functioning of the surveillance practice performed by the Public Ministry of Paraná. The material was analyzed based on the Discourse Analysis of French orientation, using the concept of discursive memory and its developments, aiming to observe the meaning effects, through an interpretative methodology. In the analysis, it was observed that the questions aim to observe how the jurors would react to certain situations, and somehow, aim to guide how they should act. One of its main functions is the containment of the senses, aiming that the interpretations of the jurors circulate among the alternatives presented. It was observed that the questionnaire produces a containment effect, through trying to limit what could be thought. As a set of questions, it is also constructed as a primer of what and how things should be interpreted in this field, producing an effect of manual, containment and warning, reminding the jurors that the defense will seek to deconstruct and prevent the realization of justice sought by the prosecution. It was observed that the questionnaire, when formulating the questions, works with the idea of a guilty and dangerous defendant. Analyzing the questionnaire and other materials that make up the analytical corpus, it was found that surveillance over opinions and information about jurors is growing to expand the accusation power of convincing. Furthermore, it matters less and less whether the defendant is guilty or innocent, since the fact of being a defendant already makes him guilty in the dominant FD.